ESTIMATION OF 305-D MILK YIELD USING REGRESSION TREE METHOD IN BROWN SWISS CATTLE - E. Eyduran; I. Yilmaz; M. M. Tariq; A. Kaygisiz (Journal of Animal and Plant Sciences, 2013)
The aim of this study is to evaluate the relationship between 305-d milk yield and several environmental factors (calving season, calving year, parity, calving interval and dry period) for Brown-Swiss dairy cattle with respect to Regression Tree method. A total of 1884 lactation records were taken from 645 Brown Swiss cattle raised at Sultansuyu State Farm, Malatya province, located in the Eastern Anatolia region of Turkiye between the years of 1987-2010. In the current paper, dry period, parity, calving interval, calving season and year were considered as explanatory variables, and 305-d milk yield was a dependent variable. Calving year was statistically the most influential factor on 305-d milk yield of the Brown Swiss cattle (F=40.468, df1=5, df2=1878, P<0.01), followed by parity and calving interval in regression tree diagram (P<0.01). The parity factor had a significant influence on 305-d milk yield of cows with lactation records included in Node 1 (F=17.606, df1=2, df2=775, P<0.01), Node 2 (F=9.530, df1=2, df2=194, P<0.01), and Node 4 (F=22.116, df1=1, df2=249, P<0.01). However, calving interval factor noticeably influenced 305-d milk yield of cows with lactation records in Node 5 (F=24.733, df1=1, df2=210, P<0.01). From Node 7 to Node 9, 305-d milk yield illustrated to be a growing trend with increasing parity. Within these cows, those having calving interval greater than 352 were observed to be higher yield with an average of 3629.345 kg. Cows with parities higher than 2 generated higher yield than the cows with parities 1 and 2. There was a statistically significant effect of the calving year, calving interval and lactation parity on 305-d milk yield in Brown-Swiss cattle. Cows including calving year 1999 in the Node 3 had the highest 305-d milk yield with an average of 4520.183 kg. No significant factor on the 305-d milk yield of cows with lactation records on calving years later than 2003 was noted in Node 6. In some cases, the 305 milk yield increased with increasing parity and calving interval. Consequently, regression tree method enabled us to get sub-homogenous groups depending upon explanatory variables from records of the Brown-Swiss dairy cattle and to identify the combinations of environmental factors which produce the highest 305-d milk yield.
Keywords: Brown Swiss; 305-d milk yield; Regression Tree Method; Least Squares Method